A Trihybrid Approach for Enhancing Crude Oil Recovery Using Effervescent‐Tablet‐Based Nanofluids - Naser Ali; Husain Bahzad; Nawaf F. Aljuwayhel; Shikha A. Ebrahim; Abbas T. Hamoud; Hussain Al‐Mazidi; Huda B. Al‐Naser; Mohammad A. Al‐Attar; Sohaib Kholosy; Ayas Al‐Zanki; Mohammad Banyan; Mumayaz Alenezi (Global Challenges)
Abstract While nanofluids can contribute enormously to enhanced oil recovery (EOR) in the upstream sector, conventional nanofluids are produced using complex equipment and expertise, which is somewhat limiting. To address this issue, herein, the use of effervescent‐tablet‐based nanofluids for EOR is reported. Tablets are formed by mixing and consolidating multi‐walled carbon nanotubes, surfactants, and effervescent agents. Both tablet‐based and conventional nanofluids are produced and then characterized for their thermal conductivities and dispersion stabilities. Thirteen recovery scenarios are investigated using a core flooding system, and include the use of single conventional fluids, steam and hot water cycles, steam with effervescent‐tablet‐based nanofluids, and steam with conventional nanofluids. Conventional or effervescent‐tablet‐based nanofluids are revealed to double the amount of extracted oil compared with other methods used in the recovery process. Tablet‐ and conventional‐nanofluid‐based recovery cycles provide 42.70% and 42.56% recovered oil, respectively, whereas conventional fluids and their cycles only extract 16.10% and 17.76%, respectively. The concentration and stability of the dispersed nanomaterial significantly affect the amount, properties, and composition of the recovered oil. Employing nanofluids composed of highly concentrated effervescent agents results in more short‐chain hydrocarbons, which indicates that effervescent‐tablet‐based nanofluids are promising for EOR use, particularly because no infrastructure modifications are required.